2022
DOI: 10.20517/mrr.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

The gut-immune-brain axis in neurodevelopment and neurological disorders

Abstract: The gut-brain axis is gaining momentum as an interdisciplinary field addressing how intestinal microbes influence the central nervous system (CNS). Studies using powerful tools, including germ-free, antibiotic-fed, and fecal microbiota transplanted mice, demonstrate how gut microbiota perturbations alter the fate of neurodevelopment. Probiotics are also becoming more recognized as potentially effective therapeutic agents in alleviating symptoms of neurological disorders. While gut microbes may directly communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…Indeed, there are examples of expression similarity such as claudin-1, claudin-12, ZO-1, ZO-2 (TJs) or VE-cadherin and α- or β-catenin (AJs), both in the brain and in the gut (Scalise et al, 2021 ). The BBB anatomy enables the ionic and metabolic exchange homeostasis, proper neurotransmitter uptake and signaling mediation, and the whole barrier integrity, while the TJs and AJs between adjacent cells restrict paracellular transport and protect the brain parenchyma from unwanted hydrophilic particles passage (Scalise et al, 2021 ; Park and Im, 2022 ). In turn, the GVB adjusts its permeability to the current state of the intestinal environment and allows the passage of needed molecules while maintaining protection from adverse molecules.…”
Section: Gut Barriers and The Blood-brain Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there are examples of expression similarity such as claudin-1, claudin-12, ZO-1, ZO-2 (TJs) or VE-cadherin and α- or β-catenin (AJs), both in the brain and in the gut (Scalise et al, 2021 ). The BBB anatomy enables the ionic and metabolic exchange homeostasis, proper neurotransmitter uptake and signaling mediation, and the whole barrier integrity, while the TJs and AJs between adjacent cells restrict paracellular transport and protect the brain parenchyma from unwanted hydrophilic particles passage (Scalise et al, 2021 ; Park and Im, 2022 ). In turn, the GVB adjusts its permeability to the current state of the intestinal environment and allows the passage of needed molecules while maintaining protection from adverse molecules.…”
Section: Gut Barriers and The Blood-brain Barriermentioning
confidence: 99%
“…On the other hand, in homeostatic condition highly specific adaptive immune response evolves throughout the host's lifespan and includes T and B lymphocytes. In a recent study, the CD4 + and CD8 + T lymphocytes were observed in the brain and accessed brain parenchyma, leading to BBB altered permeability, and neuroinflammation (Park and Im, 2022 ).…”
Section: Focusing On the Immune System- Related Signaling Pathwaysmentioning
confidence: 99%